Violences sexistes et sexuelles en École d'art - La collective d'enseignantes; H·Alix Sanyas (Glad!)
A guide to know what to do in cases of sexual and gender-based violence (SGBV) in French art schools. The guide gives legal tools to all victims and/or people wishing to help report situations of sexual harassment or assault. It provides answers to frequently asked questions about the legal and administrative framework for such situations. The guide provides information on the legal framework concerning SGBV. It dispels some of the arguments and positions frequently adopted by perpetrators (such as threatening to sue for libel) to stifle the voice of victims. The guide was written by art school teachers, based on their experience in the field. It is a feminist document. It is available in 3 versions (double-page, page-by-page, and one for low-cost home publishing on any printer) on this link : https://archive.org/details/outil-contre-les-violences-sexuelles-et-sexistes-ecole-dart-/VSS%20e%CC%81cole%20d%27art%20double%20page/mode/1up